The Correlation between Self–Efficacy and Learning Motivation on the English Speaking Ability of Secondary School Students - Indriyani, Siska; Syahid, Abdul; Qamariah, Zaitun (Lembaga Dongan Dosen, 2024)
This study investigates the correlation between self-efficacy and learning motivation in the English-speaking ability of secondary school students. Using a quantitative approach, the research employs a correlation design to explore the association among these variables. Data were collected through questionnaires assessing students' self-efficacy, learning motivation, and speaking ability. According to Creswell (2012), a quantitative descriptive design effectively identifies trends between variables within a case study framework. The findings reveal a strong positive correlation between students' English-speaking ability, self-efficacy, and learning motivation. Specifically, students with higher speaking abilities tend to exhibit greater self-efficacy and motivation, evidenced by a correlation coefficient 0.95, indicating a very strong relationship among the studied variables.